2019
DOI: 10.1002/wics.1489
|View full text |Cite
|
Sign up to set email alerts
|

On nonparametric conditional independence tests for continuous variables

Abstract: Testing conditional independence (CI) for continuous variables is a fundamental but challenging task in statistics. Many tests for this task are developed and used increasingly widely by data analysts. This article reviews the current status of the nonparametric part of these tests, which assumes no parametric form for the joint continuous density function. The different ways to approach the CI are summarized. Tests are also grouped according to their data assumptions and method types.A numerical comparison is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…The above methods are mainly for continuous data, whereas there are numerous CI tests available for discrete data as well (Agresti, 1992;Balakrishnan and Wasserman, 2018;Canonne et al, 2018;Kim and Agresti, 1997;Marx and Vreeken, 2019;Neykov et al, 2021;Yao and Tritchler, 1993). A more extensive review of CI tests can be found in Li and Fan (2020).…”
Section: Related Workmentioning
confidence: 99%
“…The above methods are mainly for continuous data, whereas there are numerous CI tests available for discrete data as well (Agresti, 1992;Balakrishnan and Wasserman, 2018;Canonne et al, 2018;Kim and Agresti, 1997;Marx and Vreeken, 2019;Neykov et al, 2021;Yao and Tritchler, 1993). A more extensive review of CI tests can be found in Li and Fan (2020).…”
Section: Related Workmentioning
confidence: 99%
“…The review over nonparametric conditional independence tests for continuous variables by Li and Fan [2020] groups the tests into the following categories.…”
Section: Introductionmentioning
confidence: 99%
“…Those limitations make these tests impractical in our context of scRNA-seq DEA and thus require adaptation. (Li and Fan, 2020) Performing DEA necessarily involves performing as many independent tests as there are genes.…”
Section: Introductionmentioning
confidence: 99%
“…Two random variables X and Y are conditionally independent given a third variable Z if, and only if, P ( X, Y | Z ) = P ( X | Z ) P ( Y | Z ). As described in Li and Fan (2020), many CIT have been developed previously and are readily available such as discretization-based tests (Margaritis (2005), Huang and others (2010)), metric-based tests (Runge (2018), Su and White (2007), Huang and others (2016)), permutation-based two-sample tests (Doran and others (2014), Gretton and others (2012), Sen and others (2017)), kernel-based tests (Muandet and others (2017), Li and others (2009)) and regression-based tests (see Li and Fan (2020) for a short review). Yet, these CIT either suffer from the curse of dimensionality or are hardly applicable to a large number of observations (Muandet and others (2017), Zhang and others (2011)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation